2003
DOI: 10.1097/01.asn.0000039565.56011.be
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroparathyroidectomy, Exogenous Calcium, and Short-Term Calcitriol Therapy on the Growth Plate in Renal Failure

Abstract: Abstract. Several factors have been implicated in the development of adynamic bone, including the use of calcium-containing phosphate binding agents, aggressive calcitriol therapy, and parathyroidectomy. To evaluate the effects of these interventions on the growth plate, weanling rats underwent sham nephrectomy (Control, n ϭ 10) and 5/6 nephrectomy (Nx). In the nephrectomized group, animals underwent (a) thyroparathyroidectomy (Nx-TPTX, n ϭ 7), (b) received exogenous calcium (Nx-Calcium, n ϭ 10), (c) received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…Compared to our previous experiments, there was a significant increase in mortality rate from 5% to 10% in our earlier studies [2,12] to approximately 25% in the current set of experiments. The rats used in this study were much younger with body weights between 50 to 60 g compared to 60 to 80 g in our previous studies.…”
Section: Resultscontrasting
confidence: 76%
“…Compared to our previous experiments, there was a significant increase in mortality rate from 5% to 10% in our earlier studies [2,12] to approximately 25% in the current set of experiments. The rats used in this study were much younger with body weights between 50 to 60 g compared to 60 to 80 g in our previous studies.…”
Section: Resultscontrasting
confidence: 76%
“…However, an increased growth plate cartilage height has not been consistently found in uremic rats. Uremic growth plate size greater than [1,6,9,11,12,14], similar to [2,4,5,8,10,11,13,14] or even smaller than [7,8] that of control animals has been reported. The reasons for this disparity are unknown.…”
Section: Introductionmentioning
confidence: 61%
“…Several studies have analyzed the tibial growth plate of young uremic rats in an attempt to clarify the mechanisms underlying growth impairment in chronic renal failure [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. There is interest in studying the growth plate in this animal model because this is where longitudinal growth takes place and it cannot be studied in children.…”
Section: Introductionmentioning
confidence: 99%
“…The height of growth cartilage has been found to be greater [1,6,9,11,12,14,15], equal [2,4,5,8,10,11,13,14,16], or smaller [7,8] than that of the control animals. The reasons for this discrepancy are not apparent, although the different animal protocols followed in these studies might, to a certain extent, explain the differences observed in the growth cartilage height.…”
Section: The Uremic Rat Gpmentioning
confidence: 91%
“…The uremic rat model has been used extensively to investigate growth impairment in chronic renal failure. However, a relatively small number of reports have focused on analysis of the modifications induced by uremia in the rat GP [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. The growing importance of autocrine and paracrine mechanisms in the hormonal control of growth adds further interest to the study of the GP in situations of growth impairment.…”
Section: Introductionmentioning
confidence: 99%